Sugarcane: Biorefinery, technology, and perspectives - Guerra, Saulo Philipe Sebastião [UNESP]; Denadai, Marcelo Scantamburlo; Saad, André Luiz Merthan [UNESP]; Spadim, Emanuel Rangel; Da Costa, Marcius Xavier Rodrigues (Elsevier, 2019)
The sugarcane in Brazil presents an economical importance since the colonial period from the 16th century, being that the first seedlings came from the Portuguese and were cultivated in the northeast region, being an agricultural landmark for the production of sugar and industrial in the country. The Brazilian sugar was exported mainly to the European countries, fertile soil, where large tracts of land and favorable climate favored a cultural productivity.
Keywords: Biofuel; Biomass; Economical importance; Sugar-energy sector; Water content